Chitosan-based hemostatic sponges as new generation hemostatic materials for uncontrolled bleeding emergency: Modification, composition, and applications. (1st July 2023) - Liu, Zhicheng; Xu, Yanzi; Su, Huining; Jing, Xunan; Wang, Daquan; Li, Shaohui; Chen, Yang; Guan, Hao; Meng, Lingjie
Abstract: The choice of hemostatic technique is a curial concern for surgery and as first-aid treatment in combat. To treat uncontrolled bleeding in complex wound environments, chitosan-based hemostatic sponges have attracted significant attention in recent years because of the excellent biocompatibility, degradability, hemostasis and antibacterial properties of chitosan and their unique sponge-like morphology for high fluid absorption rate and priority aggregation of blood cells/platelets to achieve rapid hemostasis. In this review, we provide a historical perspective on the use of chitosan hemostatic sponges as the new generation of hemostatic materials for uncontrolled bleeding emergencies in complex wounds. We summarize the modification of chitosan, review the current status of preparation protocols of chitosan sponges based on various composite systems, and highlight the recent achievements on the detailed breakdown of the existing chitosan sponges to present the relationship between their composition, physical properties, and hemostatic capacity. Finally, the future opportunities and challenges of chitosan hemostatic sponges are also proposed.